ANALISIS PENGENDALIAN MUTU PAKAN AYAM PETELUR: STUDI KASUS DI PETERNAKAN AYAM PETELUR DI KECAMATAN MIJEN KOTA SEMARANG - Barus, Oktavianus; Sulistiyanto, Bambang; Utama, Cahya Setya; Haidar, Muhammad Fikri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
The purpose of the study was to analyze the quality control of starting from the procurement of raw materials, processing, packaging and storage of laying hens feed at the Laying Chicken Farm, Mijen District, Semarang City. The material in the research is various types of feed ingredients. The research method uses data collection (actively participating in work and interviewing 4 respondents/owners and employees) and data analysis (testing the content of feed products and analysis of cause and effect). The results showed that the quality control of Laying Chicken Farm raw materials was carried out by organoleptic observation by looking at the color suitability, and biting and smelling the aroma to determine the quality. Processing quality control is carried out by sanitizing processing equipment and premises before use. The processing is done manually, by mixing feed ingredients based on their quantity. Quality control of packaging is carried out using bucket containers. Quality control of feed storage is carried out by packing feed in buckets and partly in bulk form, with a maximum shelf life of 7 day. The results of analytical research using causal diagrams, it is known that quality control in Laying Chicken Farms is influenced by 4 main factors, namely raw material factors, tools factor, method factor and human factor. The conclusion of this research is that the quality control of the procurement of raw materials, processing, packaging and storage of feed in Laying Chicken Farms is still not optimal, because it does not apply the principle of quality control in each process..